POTENTIAL AND PERFORMANCE OF SMALLHOLDER LIVESTOCK BUSINESS IN ACEH PROVINCE - Jamilah, Jamilah (Jurnal Aplikasi Manajemen, 2017)
The study aims to analyze the potential and performance of smallholder livestock business in Aceh Province. Analysis of the potential and performance of smallholder livestock business was carried out by using quantitative descriptive approach and qualitative descriptive approach. This study was conducted using purposive based on livestock production centers in Aceh, namely Aceh Besar Regency (beef cattle), North Aceh (broilers and ducks), and East Aceh (laying hens). The results showed that the Aceh province has the potential of natural resources and human resources to support the development of livestock, including the potential use of agricultural waste, food and agro-industry is very large and the high demand for meat and eggs annually. Aceh has the legal legislation in the form of law and regulations (qanun) for the development investment of livestock sector. Problems encountered in the development of animal husbandry is the limited availability and low quality of livestock as well as the pattern of development that has not business oriented and result in lower production and productivity of livestock in Aceh, not optimal utilization of human resources, limited infrastructure, and lack of supervision of the relevant institutions. Aceh government's efforts to increase the production and productivity of livestock yet provide optimal results; the indicator is not yet achieved self-sufficiency in meat and eggs need remains largely supplied from outside Aceh.